2007
DOI: 10.1161/01.hyp.0000255954.80025.34
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Endothelial Nitric Oxide Synthase Phosphorylation and Activation by Thrombin

Abstract: Abstract-Thrombin has been shown to activate endothelial NO synthase (eNOS) leading to endothelium-dependent vasorelaxation. In addition to its activation by Ca 2ϩ /calmodulin, eNOS has several regulatory sites. Ser 1179 phosphorylation of eNOS by the phosphatidylinositol 3-kinase-dependent Akt stimulates its catalytic activity. In this study, we have elucidated the signaling mechanism of thrombin-induced phosphorylation of eNOS in the regulation of NO production. Immunoblot analysis showed that thrombin rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 38 publications
(35 reference statements)
6
75
2
1
Order By: Relevance
“…However, calcium, PKA, and PKC have also been reported to phosphorylate eNOS on S1177 in response to various stimuli (12,20,39). Similarly, we have found that a PKC inhibitor, rottlerin, leads to the inhibi- The role of alternate pathways in allowing the phosphorylation of eNOS may therefore explain how VEGF and hyperactivated VEGFR2 can induce increased phosphorylation of eNOS in DEP-1-depleted cells, in which Akt activation is suboptimal.…”
Section: Discussionmentioning
confidence: 53%
“…However, calcium, PKA, and PKC have also been reported to phosphorylate eNOS on S1177 in response to various stimuli (12,20,39). Similarly, we have found that a PKC inhibitor, rottlerin, leads to the inhibi- The role of alternate pathways in allowing the phosphorylation of eNOS may therefore explain how VEGF and hyperactivated VEGFR2 can induce increased phosphorylation of eNOS in DEP-1-depleted cells, in which Akt activation is suboptimal.…”
Section: Discussionmentioning
confidence: 53%
“…47 However, the eNOS protein expression does not directly correlate with NO production since the protein must be activated to produce NO. 48 The amount of NO produced by CB-EPCs and HAECs increased significantly after exposure to fluid shear stress for both substrates, and there was no significant difference in the amount of NO produced by the two cell types. While cultured SMCs alone do produce NO in response to fluid shear stress by neuronal NOS, 49 SMCs in coculture are not exposed to shear stress directly and the similarity in the levels of NO produced with and without SMC coculture suggests that SMC NO production was not significant.…”
Section: Cord Blood Endothelial Progenitor Cellsmentioning
confidence: 86%
“…5 Previously, others have shown that PKCd phosphorylates serine (1177/1179) resulting in eNOS activation in bovine aortic endothelial cells. 38 Attenuation of PKCd (via small interfering RNA) decreased NO production in fibroblasts. 39 In both of these studies, the authors used Rottlerin, which at the time was thought to be the only specific inhibitor of PKCd but others have shown that Rottlerin is not specific for PKCd.…”
Section: Discussionmentioning
confidence: 99%